Dietary Patterns in Asian Indians in the United States: An Analysis of the Metabolic Syndrome and Atherosclerosis in South Asians Living in America Study - Gadgil, Meghana D.; Anderson, Cheryl A.M.; Kandula, Namratha R.; Kanaya, Alka M. (Journal of the Academy of Nutrition and Dietetics, 2014)
Dietary patterns contribute to cardiovascular disease (CVD) risk. Asian Indians have earlier onset, more severe, and more prevalent CVD than many other racial/ethnic groups. We aimed to characterize dietary patterns in Asian Indians living in the United States and examine associations with cardiometabolic risk factors. One hundred fifty Asian Indians, aged 45 to 84 years, without known CVD, living in the San Francisco Bay, CA, area between August 2006 and October 2007 were enrolled into the Metabolic syndrome and Atherosclerosis in South Asians Living in America study. A food frequency questionnaire validated in Asian Indians, fasting blood samples, and computed tomography scans were obtained for all participants. Principal component analysis with varimax rotation was used to determine prevalent dietary patterns. Linear regression analyses were performed for associations between dietary patterns and metabolic factors, adjusting initially for age and sex, then additionally for BMI, income, education, metabolic equivalent of task-minutes of exercise, alcohol consumption, and smoking. Two distinct dietary patterns were identified that we termed “Western,” and “Vegetarian.” Compared with the Western diet, the Vegetarian diet was associated with lower homeostasis model of assessment-insulin resistance (−1.12 mmol/L×mU/L; P=0.05) and lower high-density lipoprotein cholesterol (−4.77 mg/dL; P=0.09). Given that the Western and Vegetarian dietary patterns were each associated with adverse metabolic changes, healthful diet choices may help Asian Indians improve risk factors for CVD.